The CEO difference : how to climb, crawl, and leap your way to the next level of your career - Benton, D. A. (Debra A.) (McGraw Hill-Ascent Audio, 2014)
Stay relevant, stay connected, STAY AHEAD OF THE GAME. When it comes to getting ahead today, your talent and experience matter. The problem is, someone else going for the promotion or business opportunity has a resume that's as good as, if not better than, yours. If you want to get ahead, you have to be different. You have to stand out from the crowd. You have to get decision makers to talk about you. No one understands what it takes to succeed in today's business landscape better than D. A. (Debra) Benton. A globally recognized consultant, Benton has spent more than 20 years helping business professionals like you perform better and achieve more. In The CEO Difference, Benton gives you the insight and tools to make subtle changes in your presentation, attitude, and leadership style that will dramatically increase your leadership effectiveness-and, consequently, help you enjoy work and life. Learn how to differentiate yourself with tangible steps to get where you want to go: Authentically and effectively differentiate yourself in appropriate ways Inspire teams and organizations to be more productive and prosperous Understand yourself, change your mindset, and present yourself in a way that people are receptive to Create, manage, and mentor successful individuals and teams Remain intellectually curious while making meaningful contributions to your organization Competition for the top spot has never been fiercer. "Today, you have to exceed in a group of 'exceeders,'" Benton writes. But it's not all about improving your job performance. You are already knowledgeable, competent, and hard-working. It's about doing typical things in atypical ways. It's about doing things that add organizational value-without being asked. It's about having what your competitors don't: The CEO Difference.